Embeddings or disembeddings? A discussion about Physical education and proposals for high school - Machado, Roseli Belmonte; da Fonseca, Denise Grosso; Tavares, Natacha da Silva (Journal of Physical Education (Maringá), 2020)
In addition to discussing Physical Education and its curricula from the advent of recent educational policies, this article also proposes to move an important debate on the last stage of Basic Education, High School. This article presents analyses developed from the research that aimed to reflect on the inclusion of Physical Education in the Languages Area, discussing the relationship between the curricular proposals for Basic Education and the pedagogical practice of Physical Education teachers in High School. The methodology was based on Foucault’s studies. We intend to show that projects for training and formatting individuals have been placed in society and the current Brazilian reality, especially in the case of secondary education. We understand that these training projects are transposed with other discourses in order to gain the empathy and compliance of the population, which had long been questioning the organization and the teaching model. However, this is in fact a setback because, instead of reformulating methodologies and allowing knowledge to make sense for students, it causes them to remove from their formation that which does not seem interesting or useful to them, and, if in the future these individuals identify those gaps, they will be solely responsible for solving them.